Ward Variant of High Expressed Emotions Discovered in a Health Worker Admitted in a Tertiary Hospital in South West Nigeria - Adekeye A, Akinshade A., Akinbote J, Elegbede A, Akanbi S, Lawal M, (International Journal of Innovative Research in Medical Science, 2018)
High Expressed Emotion (HEE) is a collection of distinct attitudinal expressions characterized by critical, hostile and emotionally over-involved attitude towards a family member with a psychotic disorder, though more common with schizophrenia. It is however pertinent to state that, EE has also been documented between health workers and patients in the hospital and community settings. The Camberwell Family Interview (CBI) and its modified versions are objectively used to assess the expressed emotion (EE) in such situations. We report an interesting case of a young female health worker subjected to classical features of high expressed emotions in a hospital ward setting.